The Role and Position of AI Evidence in Civil Litigation - Sokolova, Mariia (Medicine, Law & Society, 2023)
This article examines the role and position of AI evidence in civil litigation. Despite the sporadic appearance of such evidence in court proceedings, it has the potential to revolutionize the evidential field and change our understanding of the nature and evidential qualities of existing types of evidence. After a thorough examination of the key technical specifications of AI, different classifications of AI evidence and various approaches to treatment of AI evidence, the author suggests how AI evidence should be treated according to the Slovenian Civil Procedure law. It is inferred that standard evidence rules can be applied to AI evidence, if the probative value of such evidence does not depend on the AI involved. In cases where probative value of evidence depends on the involved AI system, AI evidence can nevertheless be treated as witness or expert evidence, or, precisely, as ex parte affidavit or private expert opinion depending on the level of human or AI contribution to the content of AI evidence. The author concludes that black box and bias problems of AI systems generating evidence have to be properly addressed in order for AI evidence to achieve full evidential value and reliability.